THE EFFECT OF INSTRUMENTAL MUSIC GUIDED IMAGERY THERAPY ON THE LEVEL OF HEADACHE - Pitaloka, Dyah; Hyan Oktodia Basuki; Suhartono (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: One of the most common degenerative diseases among the elderly is hypertension. Headaches are one of the symptoms of hypertension; if not addressed promptly, headaches in hypertensive patients can lead to sleep disturbances, anxiety, emotional instability, and ultimately affect the patient's quality of life. One non-pharmacological management that can be employed to address headaches is guided imagery therapy with instrumental music. The aim of this study is to analyze the effect of guided imagery therapy with instrumental music on the level of headaches in elderly hypertensive patients in Dusun Krajan, Desa Bektiharjo, Semanding. Method: The research design in this study is a quantitative pre-experimental using the one group pre-test post-test design method. The population in this study consists of elderly hypertensive patients experiencing headaches, totaling 25 elderly individuals, with a sample selected through purposive sampling technique, resulting in a sample of 23 elderly individuals. Result: The results of the conducted research showed that elderly individuals with mild headache levels after undergoing therapy for 3 consecutive days exhibited a decrease in pain levels. After being analyzed using the Wilcoxon test with a significance level of α=<0.05, with a p-value of 0.000<0.05, the result obtained was an Asymp sig (2-tailed) value of 0.000. Conclusion : It can be concluded that H1 is accepted, which means that guided imagery therapy with instrumental music has an effect on the level of headache in elderly hypertensive patients in Dusun Krajan, Desa Bektiharjo, Semanding. The guided imagery technique is a method that helps achieve deep relaxation, creating relaxation in various ways that can control the nervous system, ultimately lowering blood pressure, thereby alleviating headaches caused by elevated blood pressure.